Developing an Inclusive Pesantren Curriculum through the Integration of the Hidden and Formal Curricula - Nurdianzah Erry; khotijah siti; Azizah Nurul (Pascasarjana Universitas Wahid hasyim Semarang, 2026)
Islamic boarding schools (pesantren) possess a distinctive educational system that integrates formal learning with boarding life to foster students' character development. However, curriculum implementation in inclusive pesantren remains predominantly focused on the formal curriculum, while the hidden curriculum embedded in the boarding school culture has not been systematically integrated into curriculum design. This study aims to develop an inclusive pesantren curriculum model based on the integration of the hidden curriculum and the formal curriculum to promote holistic, inclusive, and character-oriented learning. The study employed an Educational Design Research (EDR) approach consisting of needs analysis, model design, conceptual validation, and model refinement. The conceptual findings indicate that the hidden curriculum is manifested through the exemplary leadership of kiai, the culture of adab (Islamic ethics), boarding school life, religious habituation, social interaction, and organizational culture, all of which contribute significantly to students' character formation. Meanwhile, the formal curriculum primarily supports academic achievement but remains insufficiently connected to the learning experiences embedded in pesantren life. This study proposes an integrated curriculum model that combines learning objectives, formal instruction, pesantren culture, daily habituation, inclusive learning support, and authentic assessment into a coherent educational system. The proposed model provides a conceptual framework for developing a more adaptive, inclusive, and value-based curriculum while preserving the distinctive educational traditions of pesantren.